Modeling visual search behavior of breast radiologists using a deep convolution neural network - Mall, Suneeta (J Med Imaging (Bellingham), 2018)
Visual search, the process of detecting and identifying objects using eye movements (saccades) and foveal vision, has been studied for identification of root causes of errors in the interpretation of mammograms. The aim of this study is to model visual search behavior of radiologists and their interpretation of mammograms using deep machine learning approaches. Our model is based on a deep convolutional neural network, a biologically inspired multilayer perceptron that simulates the visual cortex and is reinforced with transfer learning techniques. Eye-tracking data were obtained from eight radiologists (of varying experience levels in reading mammograms) reviewing 120 two-view digital mammography cases (59 cancers), and it has been used to train the model, which was pretrained with the ImageNet dataset for transfer learning. Areas of the mammogram that received direct (foveally fixated), indirect (peripherally fixated), or no (never fixated) visual attention were extracted from radiologists’ visual search maps (obtained by a head mounted eye-tracking device). These areas along with the radiologists’ assessment (including confidence in the assessment) of the presence of suspected malignancy were used to model: (1) radiologists’ decision, (2) radiologists’ confidence in such decisions, and (3) the attentional level (i.e., foveal, peripheral, or none) in an area of the mammogram. Our results indicate high accuracy and low misclassification in modeling such behaviors.